2016
DOI: 10.1089/cyber.2016.0248
|View full text |Cite
|
Sign up to set email alerts
|

Selective Self-Presentation and Social Comparison Through Photographs on Social Networking Sites

Abstract: Through social media and camera phones, users enact selective self-presentation as they choose, edit, and post photographs of themselves (such as selfies) to social networking sites for an imagined audience. Photos typically focus on users' physical appearance, which may compound existing sociocultural pressures about body image. We identified users of social networking sites among a nationally representative U.S. sample (N = 1,686) and examined women's and men's photo-related behavior, including posting photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
133
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(151 citation statements)
references
References 61 publications
7
133
0
11
Order By: Relevance
“…Baker and Algotra (2016) analyse the links between social networking and depression. Fox and Vendemia (2016) identify that women edit their online images more often than men and feel worse about their body image on social media. Better coherence between the true self and the Facebook self was associated with better psychological health (Grieve & Watkinson, 2016).…”
Section: Self-esteem and Self-presentation Of Mothers On Social Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…Baker and Algotra (2016) analyse the links between social networking and depression. Fox and Vendemia (2016) identify that women edit their online images more often than men and feel worse about their body image on social media. Better coherence between the true self and the Facebook self was associated with better psychological health (Grieve & Watkinson, 2016).…”
Section: Self-esteem and Self-presentation Of Mothers On Social Mediamentioning
confidence: 99%
“…Understanding online self-presentation is of importance as previous research argues that users positively enhance their self-image online to receive more positive feedback from other users (Chua and Chang, 2016;Fox & Vendemia, 2016). It is also the case with online representation of mothers as they feel under pressure to maintain an ideal image (Bartholomew et al, 2012;Jang & Dworkin, 2014.).…”
Section: Self-presentation In Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of studies investigating adolescent use of social media focus on the impact of psychological well-being. The results from these studies have found unfavorable effects, especially related to posting and viewing photos, of social media use on mental health, including: negative mood self-objectification, body dissatisfaction, social comparison, eating behaviors, decreased self-esteem, weight dissatisfaction, drive for thinness, and peer competition [9][10][11][12][13][14][15][16][17][18][19]. Even "fitspiration" images and posts that aim to inspire people to live healthy and fit lifestyles reinforce the over-valuation of physical appearance, eating concerns, and excessive exercise that could have serious negative implications on adolescents psychological and emotional health [20].…”
Section: Introductionmentioning
confidence: 99%
“…Vartotojai taip pat raginami patalpinti savo nuotraukas. Jos laikomos svarbia įvaizdžio kūrimo dalimi (Fox, Vendemia, 2016;RuedaOrtiz, Giraldo, 2016).…”
unclassified